2014
DOI: 10.1016/j.febslet.2014.06.017
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: miR‐96/HBP1/Wnt/β‐catenin regulatory circuitry promotes glioma growth

Abstract: Edited by Lukas HuberKeywords: Glioma miR-96 Wnt/b-catenin Proliferation HMG-box transcription factor 1 a b s t r a c tWe found that miR-96 is overexpressed in glioma, and its level inversely correlates with the survival of patients. The reduction in miR-96 abundance suppresses the proliferation and colony formation of glioma cells. The tumorigenicity of U-87 MG cells is reduced by miR-96 silencing. miR-96 contributes to the activation of Wnt/b-catenin pathway in glioma cells. HMG-box transcription factor 1 (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 27 publications
(30 reference statements)
2
30
0
2
Order By: Relevance
“…Neural stem/progenitor cells are actively dividing in Hbp1-deficient mice It was previously reported that Hbp1 is involved in regulation of the Wnt signaling by inhibiting the function of TCF4-β-catenin complex via physical blockade of TCF/LEF-mediated DNA binding, and functions as a growth suppressor by repressing downstream genes of the Wnt signaling and cell cycle-related genes (Tevosian et al, 1997;Gartel et al, 1998;Sampson et al, 2001;Shih et al, 2001;Kim et al, 2006;Elfert et al, 2013;Yan et al, 2014). We therefore assessed cell proliferation activity in neural stem/progenitor cells in the developing cortex.…”
Section: Cortical Neurons Are Reduced In Number Proportionately Throumentioning
confidence: 99%
See 1 more Smart Citation
“…Neural stem/progenitor cells are actively dividing in Hbp1-deficient mice It was previously reported that Hbp1 is involved in regulation of the Wnt signaling by inhibiting the function of TCF4-β-catenin complex via physical blockade of TCF/LEF-mediated DNA binding, and functions as a growth suppressor by repressing downstream genes of the Wnt signaling and cell cycle-related genes (Tevosian et al, 1997;Gartel et al, 1998;Sampson et al, 2001;Shih et al, 2001;Kim et al, 2006;Elfert et al, 2013;Yan et al, 2014). We therefore assessed cell proliferation activity in neural stem/progenitor cells in the developing cortex.…”
Section: Cortical Neurons Are Reduced In Number Proportionately Throumentioning
confidence: 99%
“…Among a variety of genes that were differentially expressed during the course of development, we hypothesized that high mobility group box transcription factor 1 (Hbp1) might be an important regulator of neurogenesis, given that it was upregulated during neurogenic stages around embryonic day 13.5 (E13.5) through embryonic day 15.5 (E15.5). Previous studies demonstrated that Hbp1 acts as a transcriptional repressor that functions as a cell cycle inhibitor by repressing downstream targets of the Wnt signaling and cell cyclerelated genes, cyclin D1 (Ccnd1), c-jun (Jun), N-myc (Mycn) and p21 (Cdkn1a) (Gartel et al, 1998;Sampson et al, 2001;Kim et al, 2006;Elfert et al, 2013;Yan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-96 и miR-155 гиперэкспрессированы при глиомах, и уровень miR-96 обратно коррелирует с выживаемостью пациентов [48,49].…”
Section: Hbp1 (Hmg-box Transcription Factor 1)unclassified
“…The procedures of the isolation and culturing of primary astrocytes have been described previously [7], which have been approved by the Ethical Review Board in the Affiliated Hospital of Medical College of Qingdao University (Qingdao, China).…”
Section: Primary Astrocytementioning
confidence: 99%
“…To study the role of miR-155 in the tumorigenesis of glioma cell lines, two different mice models were used. The details of the establishment of glioma xenografts were available in previous papers [7]. Briefly, U-87 MG glioma xenograft was established by injecting 5×10 6 cells into the flanks of 4-5-week-old male BALB/c nude mice.…”
Section: Animal Experimentsmentioning
confidence: 99%